2016
DOI: 10.1038/srep23705
|View full text |Cite
|
Sign up to set email alerts
|

Looking for hotspots of marine metacommunity connectivity: a methodological framework

Abstract: Seascape connectivity critically affects the spatiotemporal dynamics of marine metacommunities. Understanding how connectivity patterns emerge from physically and biologically-mediated interactions is therefore crucial to conserve marine ecosystem functions and biodiversity. Here, we develop a set of biophysical models to explore connectivity in assemblages of species belonging to a typical Mediterranean community (Posidonia oceanica meadows) and characterized by different dispersing traits. We propose a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 58 publications
2
64
3
Order By: Relevance
“…These areas, not included in the present study, have been suggested to be differentiated according to Lagrangian simulations48 and thus future sampling of additional locations in these northern and southern areas would help to clarify how many genetically differentiated groups are within the Adriatic and their connections. A recent study using biophysical modelling on Symphodus ocellatus , a species with similar larval characteristics as S. tinca , suggested a high larval retention and confined dispersal across a narrow geographic range, with occasional and weak connections across the two shores of the Adriatic35. This suggested that high larval retention is in accordance with our results since even using only neutral SNPs we detected north-south dispersal limitations and an east-west barrier for S.tinca within the Adriatic Sea.…”
Section: Discussionsupporting
confidence: 91%
“…These areas, not included in the present study, have been suggested to be differentiated according to Lagrangian simulations48 and thus future sampling of additional locations in these northern and southern areas would help to clarify how many genetically differentiated groups are within the Adriatic and their connections. A recent study using biophysical modelling on Symphodus ocellatus , a species with similar larval characteristics as S. tinca , suggested a high larval retention and confined dispersal across a narrow geographic range, with occasional and weak connections across the two shores of the Adriatic35. This suggested that high larval retention is in accordance with our results since even using only neutral SNPs we detected north-south dispersal limitations and an east-west barrier for S.tinca within the Adriatic Sea.…”
Section: Discussionsupporting
confidence: 91%
“…Other aspects that can further shape the structure of the different species are the distribution and the fragmentation of suitable habitats for the different species. For these reasons, species with different life history and ecology should be included into an integrated multispecies approach to implement functional and resilient conservation networks (Melià et al, ; Pascual et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Estimating population structure, pattern of connectivity and selfrecruitment in marine populations is essential to study, design and included into an integrated multispecies approach to implement functional and resilient conservation networks (Melià et al, 2016;Pascual et al, 2017).…”
Section: Implications For Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons why ecosystem connectivity may not have been central in restoration is the practical challenge of determining the relevant energetic and material inter-connections and their influences (Melia et al, 2016): i.e., what are the fluxes among proximal ecosystems, what determines variation in their magnitude and their effects, and how do you measure them? Research in tropical coastal seascapes has revealed ecosystem engineering species within some ecosystems (i.e., species that physically modify the abiotic environment Jones et al, 1994) can significantly reduce wave energy from the ocean to the land and reduce nutrient and sediment fluxes from the land to the ocean (Gillis et al, 2014a;Saunders et al, 2014;Koppel et al, 2015;Guannel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%